On the Exponential Dichotomy on R of Linear Differential Equations in R^n - Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
New results of the investigation of exponential dichotomy on the entire axis of linear differential equations in R^n are presented.